Last Interglacial Muir Point Formation, Vancouver Island, British Columbia - Hicock, Stephen (Géographie physique et Quaternaire)

(untitled) (Les Presses de l'Université de Montréal, 1990)
ABSTRACTThe Muir Point Formation probably represents the last interglacial and climatic maximum of the Late Pleistocene in southwest British Columbia. It comprises estuarine, floodplain, fluvial, alluvial fan, and debris flow lithofacies. The lower exposed part of the formation is normally magnetized and probably formed during the Brunhes Normal Polarity Chron (<790 ka BP). On the basis of similar polarity, palynology, lithologies, and stratigraphic position, the Muir Point Formation is correlated with the Whidbey Formation of northwest Washington State. It probably also correlates with the Highbury Formation under the Fraser Lowland of mainland British Columbia.These formations may be remnants of shallow marine or subaerial sediment shelves which once rimmed ancestral Strait of Georgia and Puget basins over 100 ka, but were mostly removed by later glaciations. During this time sea level may have been 10 m higher than today. The middle floodplain unit contains five pollen zones whose differences can be explained mainly by shifts in a meandering tidal stream. Throughout most of this record Douglas fir pollen is more abundant than in modern pollen rain around the study sites which indicates that paleoclimate was at least as warm and dry as present.